2013
DOI: 10.1155/2013/659391
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive-Like Property of Dichloromethane Fraction ofPimenta pseudocaryophyllusand Relevance of Monoamine Metabolic Enzymes

Abstract: Pimenta pseudocaryophyllus popularly referred to as craveiro is considered as a calming agent in different local preparations. The present study attempted to examine antidepressant-like effect of dichloromethane fraction (DF) and role of monoamine oxidase (MAO), tryptophan, and tyrosine hydroxylase. Based on the research focus, tail suspension (TS), forced swimming (FS), and open field (OF) tests were conducted after oral administration of DF (125, 250, or 500 mg/Kg). Ex vivo assay of MAO was also conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
9
0
2
Order By: Relevance
“…PCPA or saline was administered once a day for 4 consecutive days before beginning the exercise program and again on days 11-14 postoperatively. Prior studies show that repeated application of PCPA results in reduction of 5-HT in the central nervous system [20, 55]. The current study confirmed decreases in 5-HT in the brainstem using high performance liquid chromatography (HPLC) analysis (see below).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…PCPA or saline was administered once a day for 4 consecutive days before beginning the exercise program and again on days 11-14 postoperatively. Prior studies show that repeated application of PCPA results in reduction of 5-HT in the central nervous system [20, 55]. The current study confirmed decreases in 5-HT in the brainstem using high performance liquid chromatography (HPLC) analysis (see below).…”
Section: Methodssupporting
confidence: 84%
“…In order to investigate the involvement of the catecholaminergic system in the analgesic effect observed, we reduced NE and DA with AMPT, a tyrosine hydroxylase (TH) inhibitor that is a rate-limiting enzyme in the biosynthesis of catecholamines, delivered systemically as previously described [20, 55]. Interestingly, blockade of TH with AMPT (100 mg/kg, i.p.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting pellet was suspended in 1.5 mL homogenization buffer and recentrifuged at 12,500 × g and 4 o C for 15 min; the resulting pellets were resuspended in 1.0 mL homogenization buffer, stored under -20°C in aliquots and used as the source of MAO within 48 h. Total protein concentration was estimated using the method of Bradford (Bradford, 1976). The measurement of in vitro and ex vivo activity of MAO was conducted using a modified spectrophotometric method (Fajemiroye et al, 2013;Holt et al, 1997;Stafford et al, 2007).…”
Section: Monoamine Oxidase (Mao) Assay By Spectrophotometric Methodsmentioning
confidence: 99%
“…Studies using crude extracts or essential oils obtained from P. pseudocaryophyllus leaves showed a wide potential of pharmacological properties, such as antimicrobial (Lima et al, ; Paula et al, ; Custódio et al, ; Fernandes et al, ; El Assal et al, ; Suzuki et al, ; Yokomizo and Nakaoka‐Sakita, ), anxiolytic, antidepressant (Fajemiroye et al, , ), antinociceptive, anti‐inflammatory (Paula et al, ), and antioxidant (Campanini et al, , ). Additionally, Ferrari et al () have recently shown the anti‐hyperuricemic effects of P. pseudocaryophyllus extracts from leaves and branches in hyperuricemic rats.…”
Section: Introductionmentioning
confidence: 99%